MACEDONIAN STOCK MARKET EXCHANGE SUPPLY CHARACTERISTICS - Jovanovski, Kiril (KNOWLEDGE - International Journal, 2023)
Financial development is fundamental for the country's economic growth. An important question related to financial depth is the development of the stock market exchange and banking sector. A quick overview of the data and literature shows how the banking sector is dominant in the developing and Emerging market country's financial industry. Furthermore, the financial depth measured with credit to GDP and stock market exchange capitalization to GDP ratios differs significantly among countries. On average, the stock market exchange capitalization of listed companies in emerging markets is below 10% of GDP. In contrast, developed countries have a stock market exchange capitalization of more than twice their annual GDP. A developed capital market’s role in promoting economic growth is highly imperious to all countries, North Macedonia inclusive. Given the previous, this study examines the characteristics of the North Macedonia stock market exchange supply, using secondary data covering the period of 2012 to 2022. The methodological approach combines several research methods – analysis, induction, deduction, synthesis, selection, and comparison. Findings reveal the existence of low market supply due to the small number of securities in everyday trading. From the analysis, the Macedonian stock exchange supply consists of five company shares with more than 80% of the total annual turnover. In distinction, the top 3 traded companies contribute to the total market turnover by more than 60%. More so, the Macedonian stock market exchange is not recognized to provide long-term public financing for any company. The results suggest little commitment from the Macedonian market participant, especially economic policies regarding national capital market development. Policies can start with empowering the national strategy for capital market development and the recent proactive approach of the Security regulatory agencies and Macedonian stock market exchange. The paper briefly reviews the main policy recommendations for boosting the securities supply. Those efforts have prospects of raising the market capitalization to GDP ratio of its todays around 20%. With an analysis of the Macedonian stock market exchange and policy actions, the paper's conclusions are regarding policy recommendations for overcoming the challenges for stock market exchange supply development. The first step is to start with the implementation of the National Strategy for Capital Market Development. Second, market participants should do more activities regarding the company's management attitudes towards going in public and listing their companies. Third, there is more room for financial education in capital market principles. Finally, the paper gives a solid basis for further research.
Keywords: Security market, Macedonian stock market exchange, the national strategy for capital market development